2004
DOI: 10.1002/ep.10004
|View full text |Cite
|
Sign up to set email alerts
|

Soil lead bioavailability and in situ remediation of lead‐contaminated soils: A review

Abstract: The environmental risk from soil lead (Pb) is related to its bioavailability. Soil Pb bioavailability depends on the solubility of Pb solid phases and other site‐specific soil chemistry, suggesting that in situ stabilization of soil Pb can be accomplished by changing soil Pb chemistry. This paper presents a review of soil Pb bioavailability and an evaluation of in situ stabilization methods that can be used to reduce Pb bioavailability. A promising in situ approach involves the amendment of Pb‐contaminated soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
144
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(153 citation statements)
references
References 69 publications
5
144
0
4
Order By: Relevance
“…A possible explanation for component 3 comes from literature studies in which a number of research groups show that Pb derived from anthropogenic sources where significant concentrations of P also exist results in a relatively stable form in soils as chloropyromorphite (Pb 5 (PO 4 ) 3 Cl) or similar pyromorphite minerals (Hettiarachchi and Pierzynski 2004;Cotter-Howells et al 1994;Scheckel et al 2005 -Howells et al 1994). This is in agreement with the composition of component 3 which clearly contains Pb, P and possibly Ca (Fig.…”
Section: Fig 12 Chemical Element Composition Of Cised Componentsupporting
confidence: 77%
See 1 more Smart Citation
“…A possible explanation for component 3 comes from literature studies in which a number of research groups show that Pb derived from anthropogenic sources where significant concentrations of P also exist results in a relatively stable form in soils as chloropyromorphite (Pb 5 (PO 4 ) 3 Cl) or similar pyromorphite minerals (Hettiarachchi and Pierzynski 2004;Cotter-Howells et al 1994;Scheckel et al 2005 -Howells et al 1994). This is in agreement with the composition of component 3 which clearly contains Pb, P and possibly Ca (Fig.…”
Section: Fig 12 Chemical Element Composition Of Cised Componentsupporting
confidence: 77%
“…It could be speculated that the three ISCs have been formed recently and have trapped the anthropogenic Pb in the form of the pyromorphite mineral. Some studies suggest that Pb, in the form of a pyromorphite mineral, is relatively stable and not bioaccessible (Hettiarachchi and Pierzynski 2004;Scheckel et al 2005). Other studies, however, have shown that pyromorphite solubility is increased in the low pH environment found in the stomach compartment (Xie and Giamar 2007;Tang et al 2004) and that the presence of impurities and organic acids also increases its solubility (Debela et al 2010;Xie and Giamar, 2007).…”
Section: Fig 12 Chemical Element Composition Of Cised Componentmentioning
confidence: 99%
“…Lead ranked number two on the CERCLA Priority List of Hazardous Substances and was identified as a major hazardous chemical found on 47% of USEPA's National Priorities List sites (Hettiarachchi and Pierzynski 2004). In-situ remediation of lead (Pb) contaminated soils may be accomplished by changing the soil chemistry and structure with the application of microbial and phosphate amendments.…”
mentioning
confidence: 99%
“…Soil ingestion is of particular concern among children, who may ingest larger quantities of soil than adults (e.g., by putting their hands in their mouths), absorb higher levels of certain contaminants into their bloodstream [29], and are generally more sensitive to their effects. People who consume produce grown in contaminated environments also risk ingesting soil particles on the surfaces of plants [30].…”
Section: Introductionmentioning
confidence: 99%